Promoting the Insertion of Molecular Hydrogen in Tetrahydrofuran Hydrate With the Help of Acidic Additives - Nguyen, The Thuong; Pétuya, Claire; Talaga, David; Desmedt, Arnaud (Frontiers in Chemistry, 2020)
Among hydrogen storage materials, hydrogen hydrates have received a particular attention over the last decades. The pure hydrogen hydrate is generated only at extremely high-pressure (few thousands of bars) and the formation conditions are known to be softened by co-including guest molecules such as tetrahydrofuran (THF). Since this discovery, there have been considerable efforts to optimize the storage capacities in hydrates through the variability of the formation condition, of the cage occupancy, of the chemical composition or of the hydrate structure (ranging from clathrate to semi-clathrate). In addition to this issue, the hydrogen insertion mechanism plays also a crucial role not only at a fundamental level, but also in view of potential applications. This paper aims at studying the molecular hydrogen diffusion in the THF hydrate by in-situ confocal Raman microspectroscopy and imaging, and at investigating the impact of strong acid onto this diffusive process. This study represents the first report to shed light on hydrogen diffusion in acidic THF-H2 hydrate. Integrating the present result with those from previous experimental investigations, it is shown that the hydrogen insertion in the THF hydrate is optimum for a pressure of ca. 55 bar at 270 K. Moreover, the co-inclusion of perchloric acid (with concentration as low as 1 acidic molecules per 136 water molecules) lead to promote the molecular hydrogen insertion within the hydrate structure. The hydrogen diffusion coefficient—measured at 270 K and 200 bar—is improved by a factor of 2 thanks to the acidic additive.